On Abstract Economies and Their Applications - Chien-Hao Huang; Liang-Ju Chu (Abstract and Applied Analysis)
We establish a new equilibrium existence theorem of generalized abstract economies with general preference correspondences. As an application, we derive an existence theorem of generalized quasi-variational inequalities in the general setting of -spaces without any linear structure.